Analysis of adequacy of autoregressive model for Lithuanian vowels - Kaukėnas, Jonas; Tamulevičius, Gintautas (Lietuvos matematikos rinkinys, 2016)
Autoregressive (AR) model is widely used for modeling of speech signals. Nevertheless, the problem of adequate modelling of Lithuanian speech is still open. The results of this study indicate the need of much higher order models for Lithuanian wovel description. Only high order AR models enable us to model frequential properties of Lithuanian vowels adequately.